DEVELOPMENT OF A STEM-BASED INTERACTIVE MODULE TO IMPROVE NUTRITIONAL LITERACY AND STUNTING RISK AWARENESS IN HIGH SCHOOL STUDENTS - Husnul Syafitra; A. Mushawwir Taiyeb; Asham Bin Jamaluddin; Firdaus Daud; Hartono (Jurnal Penelitian Pendidikan IPA, 2026)
Stunting remains a major nutritional challenge in Indonesia and is closely associated with low nutritional literacy among adolescents. Schools play an important role in improving students’ understanding of nutrition and health through contextual learning. However, biology learning materials are still largely limited to conventional textbooks and worksheets that do not integrate nutritional literacy and stunting issues. This study aimed to develop a STEM-based interactive module on the digestive system to improve nutritional literacy and stunting risk awareness among high school students. The study employed a Research and Development (R&D) approach using the ADDIE model. The participants were 36 Grade XI students at SMA Negeri 7 Makassar. Data were collected through expert validation sheets, teacher and student response questionnaires, nutritional literacy pretest-posttest, and stunting risk awareness questionnaires. The results showed that the module was highly valid (3.80/4.00) and highly practical (3.70/4.00). The module was also effective, as indicated by 94.44% classical learning completeness and a high N-gain score of 0.78 from pretest to posttest results. In addition, students demonstrated a very high level of stunting risk awareness (95.20%). Therefore, the STEM-based interactive module is feasible and effective for improving students’ nutritional literacy and awareness of stunting prevention.